Programming for development of tourism industry using case studies - Abdol Aziz Shahraki; Issa Ebrahimzadeh (Cogent Business & Management, 2015)
This is a research into the assessment of tourism industry quality and programing for its development in Iran. In a tough economic situation, the hypothesis is to grow and develop the national economy with the help of the tourism industry. A unified assessment of tourism industry quality, method is made use of in this study, which is based on the case study of all elements of Iran tourism industry system. Quality assessment by means of unified problems (indicators) that hinder the maximum development of the tourism industry shows the reliability of the hypothesis. SWOT analysis aided to determine the weaknesses and threats aiming at raising the quality of the indicators. In addition, a linear programming from the standpoint of internal and external relations with national economy has been applied. The analysis revealed that the system of the tourism industry is unable to assist the macro economy. The failure corresponds to scarcely favorable natural environmental conditions, capacity for motivating to visitors, tourism marketing, and tourism infrastructures. After remedy actions, prospects for tourism industry development despite the complicated situation are quite favorable due to the advantageous climate, natural characteristics, cultural and ancient heritages, tourism resources, and educated labor. The methods applied by this paper suggest adaptive governance tools suitable to apply for optimization of the tourism industry everywhere similar to Iran.
Keywords: 650